The Class of Homothetic Isoquant Production Functions - Clemhout, S. (Review of Economic Studies, 1968)
The Class of Homothetic Isoquant Production Functions Get access S. Clemhout S. Clemhout University of California, Berkeley Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 35, Issue 1, January 1968, Pages 91–104, https://doi.org/10.2307/2974410 Published: 01 January 1968